(untitled) (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: Carcinoma of oral tongue is the most common oral cancer and because of its structure and function is prone for early local and regional spread of cancer. The final outcome of a primary tongue carcinoma patient depends upon various prognostic factors like thickness of tumor, depth of invasion, size of lesion and neck node 67metastasis. Risk of metastasis and spread to neck nodes increases with increase in tumor thickness Methods: This prospective observational study was carried out in the Department of Otolayngology- Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka for 18 months. Thirty patients with early oral tongue carcinoma i.e.T1 & T2 as per UICC and AJC criteria were included in this study by purposive non-randomized sampling technique. Result of the study were expressed as mean, standard deviation (+SD), frequency and percentages. Unpaired Student’s t-test and Pearson’s correlation co-efficient (r) test were performed. Results: Result of the study showed the mean (+SD) thickness of the tumor was 3.62 (+1.46) mm. Minimum thickness 1.1mm and maximum thickness 7.8mm. Only 21 (70%) subjects neck node were metastasized from tongue and mean (+SD) tumor thickness of the positive neck node metastasis was 5.54 (+1.07) mm and negative neck node metastasis was 2.87 (+0.75) mm. This indicated a significant difference between the groups. Pearson’s correlation co-efficient r (+0.981) which indicated tumor thickness was positively correlated with neck node metastasis. Conclusion: Tumor thickness of the early oral carcinoma positively correlated with neck node metastasis. Correlation between thickness and metastatic lymph node can help planning the treatment regimen and indicate the disease prognosis. Bangladesh J Otorhinolaryngol; April 2021; 27(1): 25-35